Synthesis of Silicate Zeolite Analogues Using Organic Sulfonium Compounds as Structure‐Directing Agents. Issue 43 (21st August 2015) - Jo, Changbum; Lee, Sungjune; Cho, Sung June; Ryoo, Ryong
Abstract A microporous crystalline silica zeolite of the MEL structure type and three other zeolite analogues composed of germanosilicate frameworks were synthesized using tributylsulfonium, triphenylsulfonium, or tri(para‐tolyl)sulfonium as the structure‐directing agent. The germanosilicates thus obtained had ISV, ITT, or a new zeolite structure depending on the synthesis conditions. The structure of the new germanosilicate was solved using X‐ray powder diffraction data with the aid of a charge‐flipping method. The solution indicated a crystal structure belonging to the P63/mmc space group with cell parameters of a=16.2003 Å and c=21.8579 Å. After calcination, the new germanosilicate material exhibited two types of accessible micropores with diameters of 0.61 and 0.78 nm.